Experimental study on the dynamic tensile behavior and energy evolution of limestone subjected to dry-wet cycles - Dai, Wusi; Gao, Pengfei; Cheng, Bing; Pan, Cheng (Frontiers in Materials, 2025)
To investigate the effects of wet-dry cycling on the dynamic tensile strength and failure characteristics of limestone, this study conducted dynamic impact loading experiments on limestone specimens subjected to varying numbers of wet-dry cycles using a Split Hopkinson Pressure Bar (SHPB) system. By integrating digital image correlation (DIC) and fractal analysis, the stress-strain evolution, crack propagation patterns, and energy dissipation mechanisms under different loading rates and wet-dry conditions were systematically analyzed. Results indicate that wet-dry cycling significantly degrades limestone’s mechanical properties, reducing tensile strength and promoting complex crack propagation. Energy distribution and dissipation were also substantially influenced. While dynamic tensile strength improved with increasing loading rates, the weakening effect of wet-dry cycles became more pronounced. Additionally, interactions between main and secondary cracks grew more intricate with prolonged cycling. The fractal dimension of fragmentation increased linearly with cycle number, though sensitivity gradually declined. These findings advance the theoretical understanding of limestone failure mechanisms under coupled wet-dry cycling and dynamic loading. They also offer practical insights for mining engineering and blast design applications.